2017
DOI: 10.1111/1911-3838.12150
|View full text |Cite
|
Sign up to set email alerts
|

Can Language Predict Bankruptcy? The Explanatory Power of Tone in 10‐K Filings

Abstract: We examine whether the language used in 10-K filings reflects a firm's risk of bankruptcy. Our sample contains 424 bankrupt U.S. companies in the period 1994-2015 and we use propensity score matching to find healthy matches. Based on a logit model of failing and vital firms, our findings indicate that firms at risk of bankruptcy use significantly more negative words in their 10-K filings than comparable vital companies. This relationship holds up until three years prior to the actual bankruptcy filing. With ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
0
8
1
Order By: Relevance
“…There are on average 472 litigious words (LIT_NUM_10K t−1 ) used in 10-K reports, representing an average of about 0.67 percent 4 of total average words in 10-K reports of our sample firms. The percentage of litigious words in our sample firms is considerably lower than the percentage of 2.08 percent reported by Lopatta et al (2017) for bankrupt firms from 1993 to 2013. This suggests that failing firms face significantly more legal issues compared with healthy firms (Lopatta et al, 2017).…”
Section: Descriptive Statisticscontrasting
confidence: 75%
See 2 more Smart Citations
“…There are on average 472 litigious words (LIT_NUM_10K t−1 ) used in 10-K reports, representing an average of about 0.67 percent 4 of total average words in 10-K reports of our sample firms. The percentage of litigious words in our sample firms is considerably lower than the percentage of 2.08 percent reported by Lopatta et al (2017) for bankrupt firms from 1993 to 2013. This suggests that failing firms face significantly more legal issues compared with healthy firms (Lopatta et al, 2017).…”
Section: Descriptive Statisticscontrasting
confidence: 75%
“…The percentage of litigious words in our sample firms is considerably lower than the percentage of 2.08 percent reported by Lopatta et al . (2017) for bankrupt firms from 1993 to 2013. This suggests that failing firms face significantly more legal issues compared with healthy firms (Lopatta et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sentiment (i.e., tone) of messages reflected in annual reports (Henry, 2008;Huang et al, 2014;Yekini, Wisniewski, & Millo, 2016) tends to influence investors' and analysts' views about firms. Similarly, one can argue that annual report tone would be associated with audit risk assessment (see Lopatta, Gloger, & Jaeschke, 2017;Yang, Yu, Liu, & Wu, 2018), as, for example, auditing standards require auditors' perusal of information that accompanies audited financial statements (International Federation of Accountants, 2012). Nevertheless, whether the overall tone reflected in the reports is associated with auditor's decisions remains yet to be empirically examined.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the annual report's more negative sentiment is associated with larger delisting probabilities, lower odds of paying subsequent dividends, higher subsequent loan loss provisions, and lower future return on assets. Similarly, Lopatta, Gloger, and Jaeschke (2017) concluded that firms at risk of bankruptcy use significantly more negative words in their 10-K filings than comparable vital companies. This relationship holds up until three years before the actual bankruptcy filing.…”
Section: Related Workmentioning
confidence: 99%